Perbaikan Proses Bisnis Order-to-Cash dan Procure-to-Pay di PT. Soka Cipta Niaga - Alfin Rizky Rachman 10070218064; Reni Amaranti; Ahmad Arif Nurrahman (Bandung Conference Series: Industrial Engineering Science, 2026)
Abstract. The Order-to-Cash (O2C) and Procure-to-Pay (P2P) processes at PT. Soka Cipta Niaga face inefficiencies such as stock data mismatches, poor interdepartmental communication, duplicate entries, shipment delays, incorrect goods received, late payments, and weak system integration. This study aims to evaluate current workflows and propose improvements to achieve greater efficiency and integration. A single case study with a descriptive qualitative approach was conducted, applying the Business Process Improvement (BPI) framework and Business Process Model and Notation (BPMN) to model as-is and to-be processes. Value Added Assessment (VAA) was used to identify activities with little or no value, while the ESIA technique (Eliminate, Simplify, Integrate, Automate) guided redesign efforts. The to-be models were simulated using Bizagi Modeler to measure improvements. Findings show that eliminating duplicate entries, automating manual approvals, and integrating systems reduced O2C cycle time by 21.67% and P2P by 32.45%. The redesigned processes deliver streamlined, faster, and integrated workflows, offering insights for other manufacturing firms to enhance operational efficiency. Abstrak. Proses Order-to-Cash (O2C) dan Procure-to-Pay (P2P) di PT. Soka Cipta Niaga masih menghadapi berbagai inefisiensi, seperti ketidaksesuaian data stok, komunikasi antar divisi yang kurang efektif, pencatatan ganda, keterlambatan pengiriman, kesalahan penerimaan barang, keterlambatan pembayaran, serta rendahnya integrasi sistem. Penelitian ini bertujuan mengevaluasi kondisi aktual serta merancang perbaikan agar lebih efisien dan terintegrasi. Metode yang digunakan adalah studi kasus tunggal dengan pendekatan deskriptif kualitatif, menggunakan kerangka kerja Business Process Improvement (BPI) dan Business Process Model and Notation (BPMN) untuk memodelkan proses as-is dan to-be. Analisis aktivitas dilakukan dengan Value Added Assessment (VAA), sedangkan teknik ESIA (Eliminate, Simplify, Integrate, Automate) diterapkan untuk menyederhanakan, menghapus, mengintegrasikan, dan mengotomatisasi proses. Simulasi menggunakan Bizagi Modeler menunjukkan perbaikan signifikan, yaitu pengurangan waktu siklus O2C sebesar 21,67% dan P2P sebesar 32,45%. Hasilnya, rancangan proses bisnis usulan menghasilkan alur kerja yang lebih ringkas, cepat, dan terintegrasi, serta dapat menjadi acuan bagi perusahaan manufaktur lain dalam meningkatkan efisiensi operasional.